Flavonoid Library Screening Reveals Kaempferol as a Potential Antiviral Agent Against African Swine Fever Virus - Arabyan, Erik; Hakobyan, Astghik; Hakobyan, Tamara; Grigoryan, Rafaella; Izmailyan, Roza; Avetisyan, Aida; Karalyan, Zaven; Jackman, Joshua A.; Ferreira, Fernando; Elrod, Charles C.; Zakaryan, Hovakim (Frontiers in Microbiology, 2021)
Naturally occurring plant flavonoids are a promising class of antiviral agents to inhibit African swine fever virus (ASFV), which causes highly fatal disease in pigs, being a major threat to the swine industry. Currently known flavonoids with anti-ASFV activity demonstrate a wide range of antiviral mechanisms, which motivates exploration of new antiviral candidates within this class. The purpose of this study was executed to determine whether other flavonoids may significantly inhibit ASFV infection in vitro. We performed a cell-based library screen of 90 flavonoids. Our screening method allowed us to track the development of the virus-induced cytopathic effect by MTT in the presence of tested flavonoids. This screening method was shown to be robust for hit identification, with an average Z-factor of 0.683. We identified nine compounds that inhibit ASFV Ba71V strain in Vero cells. Among them, kaempferol was the most potent and exhibited dose-dependent inhibition, which occurred through a virostatic effect. Time-of-addition studies revealed that kaempferol acts on the entry and post-entry stages of the ASFV replication cycle and impairs viral protein and DNA synthesis. It was further identified that kaempferol induces autophagy in ASFV-infected Vero cells, which is related to its antiviral activity and could be partially abrogated by the addition of an autophagy inhibitor. Kaempferol also exhibited dose-dependent inhibition of a highly virulent ASFV Arm/07 isolate in porcine macrophages. Together, these findings support that kaempferol is a promising anti-ASFV agent and has a distinct antiviral mechanism compared to other anti-ASFV flavonoids.